2021
DOI: 10.1002/ange.202107181
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Labeling of Legionaminic Acid in Flagellin Glycosylation of Campylobacter jejuni Identifies Maf4 as a Putative Legionaminyl Transferase

Abstract: Campylobacter jejuni is the major human food‐borne pathogen. Its bipolar flagella are heavily O‐glycosylated with microbial sialic acids and essential for its motility and pathogenicity. However, both the glycosylation of flagella and the exact contribution of legionaminic acid (Leg) to flagellar activity is poorly understood. Herein, we report the development of a metabolic labeling method for Leg glycosylation on bacterial flagella with probes based on azide‐modified Leg precursors. The hereby azido‐Leg labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Since flagellin glycosylation was far more efficient when cells only produced Leg, we infer that a functional Pse biosynthesis pathway could interfere with Leg production, perhaps at the junction that consumes UDP-GlcNAc. Alternatively, CMP-Pse and CMP-Leg could both competitively bind to FlmG Cc-Bs It will be interesting to conduct similar dissection experiments with the other class of fGTs that are wide-spread in bacteria, the Mafs (van Alphen et al, 2008;Parker et al, 2014;Sulzenbacher et al, 2018;Khairnar et al, 2020;Meng et al, 2021), to test if a similar re-programming in donor specificity is possible once the corresponding determinants have been identified. An X-ray structure determined for the Maf from M. magneticum (Sulzenbacher et al, 2018) revealed a tripartite domain architecture with central GT-A domain bearing clear resemblance to the GT29 and GT42 family of sialyltransferases.…”
Section: Specificity Determinants In Flagellin Glycosyltransferasesmentioning
confidence: 99%
“…Since flagellin glycosylation was far more efficient when cells only produced Leg, we infer that a functional Pse biosynthesis pathway could interfere with Leg production, perhaps at the junction that consumes UDP-GlcNAc. Alternatively, CMP-Pse and CMP-Leg could both competitively bind to FlmG Cc-Bs It will be interesting to conduct similar dissection experiments with the other class of fGTs that are wide-spread in bacteria, the Mafs (van Alphen et al, 2008;Parker et al, 2014;Sulzenbacher et al, 2018;Khairnar et al, 2020;Meng et al, 2021), to test if a similar re-programming in donor specificity is possible once the corresponding determinants have been identified. An X-ray structure determined for the Maf from M. magneticum (Sulzenbacher et al, 2018) revealed a tripartite domain architecture with central GT-A domain bearing clear resemblance to the GT29 and GT42 family of sialyltransferases.…”
Section: Specificity Determinants In Flagellin Glycosyltransferasesmentioning
confidence: 99%
“…Similar dissection experiments should be conducted with the other class of fGTs that are wide-spread in bacteria, the Mafs [10, 26, 28, 47, 48], to reveal if analogous mechanisms and determinants underpin flagellin glycosylation in these systems. It stands to reason that donor and acceptor specificities exist in Mafs as well, however, the flagellin recognition determinants remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Pse or Leg are constituents of capsular polysaccharides (CPS or K-antigen) [4] or the Oantigen of lipopolysaccharide (LPS) [5], but they often also occur conjugated to proteinaceous surface appendages, for example on the subunits of S-layer arrays [6], pilus adhesins [7] or flagellar filaments (the H-antigen) [8,9]. Pse and Leg derivatives synthesized in vitro can be added exogenously in metabolic labeling experiments to be incorporated into bacterial surface structures [10,11]. Moreover, Pse and Leg are attractive vaccine targets as shown by the recent report that mice immunized with Pse chemically conjugated to a carrier protein were protected against the Pse-containing pathogenic Acinetobacter baumannii strain Ab-00.191 [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations